Med Moth: A Storytelling Platform for Improving Wellness in Medical Education - Michelle Silver; Sarah Ohnigian; Hugh Silk; Michael Ennis; Judith Savageau (University Library System, University of Pittsburgh, 2022)
Background: Burnout is a major issue amongst medical students and professionals that demands a solution. Mindfulness has been shown to decrease burnout. Storytelling, as a form of mindfulness, leads to reflection. Few publications have studied the effect of storytelling on student and clinician wellness. To address wellness within their medical community and utilize the underexplored method of narrative medicine as a curricular enhancement, the authors designed and implemented a novel storytelling platform, Med Moth, at the University of Massachusetts Medical School (UMMS) and associated hospital (UMass Memorial Medical Center). Methods: Members of the community were invited to storytelling events to listen to and share stories about formative medical experiences. Four events were held between 2017 and 2018. After each event, participants received a survey inquiring how attendance benefitted them personally and professionally. Results: Clinicians, students, and faculty comprised the 104 first-time attendees surveyed. Med Moth produced a strong perceived benefit to surrogate measures including emotional exhaustion and depersonalization, defining characteristics of burnout, and professional development. Among these three measures, 66% of participants rated 4-5 (out of 5). Nearly all attendees (96%) rated 4-5 for the overall experience. Lastly, medical students reported a higher benefit regarding professional development than clinicians (p=0.002). Conclusions: This pilot study of a novel storytelling platform demonstrates positive personal and professional development outcomes, both during and after medical school training. Medical schools, residency programs, and medical institutions should strongly consider the implementation of such a wellness platform to build resiliency and to mitigate burnout through reflection.